Simulation of the Internal Structure of a Tandem-Type Plasmatron - Essiptchouk, A. [UNESP]; Charakhovski, L. (Springer Nature, 2018)
Numerical simulation of a tandem-type plasmatron intended for supersonic plasma spraying of metallic and ceramic materials at atmospheric pressure has been carried out. The calculation results are compared with experimental data. The internal gas dynamics of the plasmatron and the interaction of a plasma stream with spray particles are presented in the form of distributions of the main thermal and kinetic characteristics of stream.
Keywords: cold spraying; computer simulation; high-velocity plasma spraying; plasma powder spraying